2017
DOI: 10.1038/s41598-017-10349-3
|View full text |Cite
|
Sign up to set email alerts
|

IRF2BP2-deficient microglia block the anxiolytic effect of enhanced postnatal care

Abstract: Enhanced postnatal care (EPC) increases resilience to adversity in adulthood. Since microglia participate in shaping neural circuits, we asked how ablation of an inflammation-suppressing factor IRF2BP2 (Interferon Regulatory Factor 2 Binding Protein 2) in microglia would affect the responses to EPC. Mice lacking IRF2BP2 in microglia (KO) and littermate controls (WT) were subjected to EPC during the first 3 weeks after birth. EPC reduced anxiety in WT but not KO mice. This was associated with reduced inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…IRF2BP2‐deficient macrophages showed enhanced inflammatory phenotype and worsened atherosclerosis in mice . Similarly, loss of IRF2BP2 in microglia, the brain‐resident macrophages, leads to an enhanced inflammatory phenotype . In addition, a gain‐of‐function mutation of IRF2BP2 is proposed as a cause for a familial form of common variable immunodeficiency disorder .…”
Section: Discussionmentioning
confidence: 99%
“…IRF2BP2‐deficient macrophages showed enhanced inflammatory phenotype and worsened atherosclerosis in mice . Similarly, loss of IRF2BP2 in microglia, the brain‐resident macrophages, leads to an enhanced inflammatory phenotype . In addition, a gain‐of‐function mutation of IRF2BP2 is proposed as a cause for a familial form of common variable immunodeficiency disorder .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the IRF2BP proteins have emerged as important factors in the immune system. They can suppress inflammation in macrophages and microglia (Chen et al, 2015;Cruz et al, 2017;Hari et al, 2017) and have inhibitory effects on the expression of the programmed death ligand 1 (PD-L1) (Dorand et al, 2016;Soliman et al, 2014;Wu et al, 2019). Furthermore, IRF2BP2 was found to regulate the Hippo pathway in liver cancer and to act as a tumor suppressor (Feng et al, 2019).…”
Section: Egf Stimulation Induces Transient Desumoylation Of Several Tmentioning
confidence: 99%
“…These data suggest a specific function for IRF2BP2 in IFN‐β signaling . In addition, the same group demonstrated that IRF2BP2 in microglia is necessary for the anxiety‐reducing effect of enhanced maternal care by suppressing IL‐1β expression in mice …”
Section: Irf2bp2 Protein As a Gene Expression Regulatormentioning
confidence: 85%
“…11 In addition, the same group demonstrated that IRF2BP2 in microglia is necessary for the anxiety-reducing effect of enhanced maternal care by suppressing IL-1 expression in mice. 12 It is important to highlight the study performed by Arruda and colleagues 16 that reported that multiple sclerosis is characterized by high levels of microRNA associated with low levels of IRF2BP2.…”
Section: Irf2bp2 Protein As a Gene Expression Regulatormentioning
confidence: 98%
See 1 more Smart Citation